Penyusunan Strategi Operasional Pencapaian Target Penjualan Hydro Coco melalui Supply Chain Management dan Value Chain Management - , Christiana Kostan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study has two objectives, the first, aimed to determine the achievement of sales targets scenario of Hydro Coco in 2012 from the Supply Chain Management, by identifying performance measures and metrics used in each stage of the supply chain management, namely plan, source, make, deliver, return and determine the appropriate performance measures and appropriate for Hydro Coco. The second objective is to determine the proposed operational strategies and initiatives to support the achievement of sales targets of Hydro Coco in 2012 amounting to Rp 196 billion through the analysis of value chain management of the supply chain management Hydro Coco products. Research is to determine the size of the performance through supply chain management tool by collecting measures of performance of the various theories and journal references, verifications through in-depth interviews, and determine KPIs of Hydro Coco by reference and actual key performance indicators of Hydro Coco in 2011. Research by means of value chain management research was carried out by analyzing the key activities in each of the primary activities of the value chain, ranging from the availability of products on the market, warehouse capacity available today, production capacity, and the availability of raw materials. The results of this study were 33 key performance indicators selected to measure performance of Hydro Coco, and 17 key performance indicators were not used by PT Kalbe Farma Tbk to measure the performance of Hydro Coco. Proposed operational strategies to achieve sales targets is through Operational Excellence approach by providing the appropriate amount of product demand from customers, accelerate product service ability to customers across through cross-docking and direct delivery to the branches, optimize the frequency of delivery of goods from factory to warehouse, production capacity, and conduct strategic sourcing, and Product Leadership, by focusing on continuous improvement in innovation for Hydro Coco products.